Revitalization of Occupational Safety and Health Teaching Materials Based on Life Based Learning Paradigms - Dianna Ratnawati; Setuju Setuju (Jurnal Taman Vokasi, 2019)
Revitalizing OSH (Occupational Safety and Health) teaching materials is needed in line with the essence of OSH in the scope of education, work environment, and social life. OSH teaching materials used are still learning-oriented content, while the demands of the learning paradigm have shifted to Life Based Learning (LBL). OSH teaching materials in PTM (Mechanical Engineering Education) Study Programs need to be revitalized. The purpose of this study is : (1) producing OSH teaching materials; and (2) evaluating the results of the implementation of revitalized OSH teaching materials. The method used to achieve the research objectives is the Research and Development (R&D), which adopts the ADDIE (Analysis-Design-Development-Implementation-Evaluation) model. The instrument used was a questionnaire based on the feasibility of teaching materials based on students' apperception. Topics covered in this OSH textbook include the fire chapter, First Aid for Accidents (P3K), Occupational safety and health Management System (SMK3), occupational nutrition, radioactive and noise hazards, personal protective equipment (PPE), and ergonomics. The results of expert assessments (industry OSH experts and university lecturers) obtained an average rating of 85.6% as follows. The test results on 54 students showed an average total response of 83% showed that OSH teaching materials based on the LBL paradigm were very suitable for use in tertiary institutions.